Multimode interference in single mode-multimode-single mode fiber structure for steel beam compressive strain measurement - Yusof, Nur Hotimah; Razak, Hashim Abdul; Arof, Hamzah; Harun, Sulaiman Wadi (John Wiley & Sons, 2018)
A simple optical sensor based on singlemode-multimode-singlemode (SMS) optical fiber structure is proposed and demonstrated for the measurement of steel beam compression strain. The SMS sensor probe is fabricated by splicing both ends of a short multimode fiber with two pieces of standard single-mode fibers using a fusion splicer. The strain sensitivity stems from the difference in the effective refractive index of the core, which induces resonant wavelength shift against the strain. In the experiment, parallel measurements were also made using an electrical resistance (ER) strain gauge for comparison purpose. The SMS sensor was also able to detect the elastic limit of the steel beam from the abrupt shift in the interference wavelength as the compressive strain was increased above 5.351 mm/mm. The sensor showed that the steel beam had an elastic limit at a compressive load of 130 kN, which was in good agreement with the ER strain gauge measurement. Furthermore, the SMS sensor exhibited a compressive strain sensitivity of 0.0323 nm/kN from the initial load until it reached the elastic limit.